Establishment of reference ranges for Serum Leptin and C-Peptide using enzymelinked immmunosorbent assay method: a preliminary report (Asian Journal of Medical and Biological Research, 2016)
Reference ranges (RR) or Reference Intervals (RIs) are very important values for accurate interpretation of clinical laboratory test results. Any test result that is not accompanied by a valid RR value is less informative and may not be interpreted correctly. However, reference values of most analytes for Nigerian population are not readily available. The present study aims at establishing reference values of Serum Leptin and C-Peptide for Dutse, Jigawa State. In a cross sectional study, eighty (80) reference individuals were recruited. Serum Leptin and C-Peptide were analysed using ELISA methods. Following an accepted guideline, population specific reference intervals were established for these analytes and found to be 3.13ng/mL to 14.09ng/mL for Leptin and 0.56ng/mL to 5.64ng/mL for C-Peptide, respectively. Populations sharing similar physical and socio-economic characteristics may adapt these intervals if validated and considered suitable for their laboratory methodsAsian J. Med. Biol. Res. September 2016, 2(3): 483-487